Empathy and repeat offending of young offenders in Argentina - Orlando, Mirian S. (International journal of comparative and applied criminal justice, 2023)
Low empathy is an important psychological construct for understanding persistent criminal and antisocial behavior. In this study the affective empathy (the capacity to experience the emotions of others) and cognitive empathy (the capacity to understand the emotions of others) of 100 young male offenders (aged 16-17) in Buenos Aires was assessed using the Basic Empathy Scale. The level of empathy of young offenders who were repeat offenders (N=49) was then compared to one-time offenders (N=51). In addition, data on family criminality, school achievement and socioeconomic status was also obtained for both groups. The results showed that repeat offenders had significantly lower affective and cognitive empathy, and that these relationships held independently of the other related factors. These findings suggest that low empathy may be an important explanatory factor for repeat offending of juveniles in Argentina, and therefore may be a useful target for interventions designed to reduce repeat offending